2021
DOI: 10.3390/foods10051093
|View full text |Cite
|
Sign up to set email alerts
|

Tasty but Nasty? The Moderating Effect of Message Appeals on Food Neophilia/Neophobia as a Personality Trait: A Case Study of Pig Blood Cake and Meatballs

Abstract: Given the development of food tourism, food culture has become an important motivation for tourists. This study focuses on food tourism and examines the effects of message appeal and personality traits (food neophilia or neophobia) on tourists’ willingness to consume pig blood cake (PBC) and meatballs, two rice-based Taiwanese street foods. A total of 181 valid questionnaires were administered to foreign tourists in Taiwan (the majority of subjects were Europeans and Americans) through snowball sampling. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…It was found that FB or FL of foreign tourists strongly influenced their willingness to consume rice-based Taiwanese street food. The most significant finding of this specific study with the theme of local food is that FB or FL moderates the attraction effect of the message on the intention of foreign tourists to experience local flavors [52]. In another study, based on consumer choice value theory and the theory of planned behavior, the moderator effect of FB/FL behavior was also examined.…”
Section: The Moderator Role Of Fb and Fl In The Effect Of Ds On Pdbimentioning
confidence: 88%
See 1 more Smart Citation
“…It was found that FB or FL of foreign tourists strongly influenced their willingness to consume rice-based Taiwanese street food. The most significant finding of this specific study with the theme of local food is that FB or FL moderates the attraction effect of the message on the intention of foreign tourists to experience local flavors [52]. In another study, based on consumer choice value theory and the theory of planned behavior, the moderator effect of FB/FL behavior was also examined.…”
Section: The Moderator Role Of Fb and Fl In The Effect Of Ds On Pdbimentioning
confidence: 88%
“…Another contribution of the research is related to the variables included in the model. Although the number has increased in recent years, there are very few studies that examine the food fear and food desire context of customers based on the tourism sector [52,70,76]. This paper provides empirical findings to fill the gap in the literature.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…In addition, people over the age of 18 were often students, who make up a significant proportion of the population in the study region. On the other hand, the limit value, which was the age of 40, was considered final because, according to the research conducted by the Public Opinion Research Center in Poland, the average age begins after the age of 40 [32][33][34]. The authors wanted to conduct research using the PAPI method, which is why the nearest agglomeration, which is the Tri-City, was selected.…”
Section: Selection Of the Sample Of Respondents For The Main Studymentioning
confidence: 99%